2018
DOI: 10.11606/s1518-8787.2018052000384
|View full text |Cite
|
Sign up to set email alerts
|

Eventos adversos de vacinas e as consequências da não vacinação: uma análise crítica

Abstract: OBJECTIVE:To analyze the risks related to vaccines and the impacts of non-vaccination on the world population.METHODS:This is a narrative review that has considered information present in the bibliographic databases NCBI-PubMed, Medline, Lilacs, and Scientific Electronic Library Online (SciELO), between November 2015 and November 2016. For the analysis of outbreaks caused by non-vaccination, we considered the work published between 2010 and 2016.RESULTS:We have described the main components of the vaccines off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
71

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 86 publications
0
20
0
71
Order By: Relevance
“…A review study on adverse events of vaccines provided by SUS showed that the risks associated with vaccines do not justify its disruption and that the risk associated with non-vaccination is growing. The authors also alerted the lack of information and emphasized the role of health professionals 9 . The low proportion of individuals that know the human papillomavirus and its vaccine reinforced this demand for educational interventions 28 .…”
Section: Introductionmentioning
confidence: 99%
“…A review study on adverse events of vaccines provided by SUS showed that the risks associated with vaccines do not justify its disruption and that the risk associated with non-vaccination is growing. The authors also alerted the lack of information and emphasized the role of health professionals 9 . The low proportion of individuals that know the human papillomavirus and its vaccine reinforced this demand for educational interventions 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Desse modo, cabe ressaltar aqui o dever dos profissionais da saúde e da mídia divulgar informações com amparo científico sobre o assunto, com responsabilidade ética e profissional diante da sociedade. 9 É importante frisar também que, embora haja uma política de notificação de todos os casos suspeitos de reação vacinal, há ainda um grande número de eventos subnotificados, o que prejudica o estabelecimento real dos dados estatísticos.…”
Section: Discussionunclassified
“…Tais movimentos vêm ganhando espaço na mídia informal e preocupa a população. 9 O objetivo desse presente estudo faz-se em identificar a prevalência das reações adversas da Vacina do Rotavírus Humano na cidade de Franca-SP. Espera-se determinar também, se há maiores taxas de reação na primeira ou na segunda dose da vacina e a segurança da vacina segundo os efeitos adversos.…”
Section: Introductionunclassified
“…A imunização é considerada como uma das medidas mais efetivas na prevenção de doenças imunopreveníveis por promover a diminuição da morbimortalidade (Dutra, et al, 2019). Com isso, o Programa Nacional de Imunização (PNI), instituído pela Lei nº 6.259 de 30 de outubro de 1975, é destacado como sendo um dos projetos mais completos entre os países em desenvolvimento, visto que este apresenta atualmente, 19 vacinas recomentadas pela Organização Mundial da Saúde (OMS) e são distribuídas de forma gratuita pelo Sistema Único de Saúde (SUS) (Aps, et al, 2018).…”
Section: Introductionunclassified